The feasibility analysis of cement kiln as an MSW treatment infrastructure: From a life cycle environmental impact perspective. (10th September 2020) - Kosajan, Vorada; Wen, Zongguo; Fei, Fan; Doh Dinga, Christian; Wang, Zhaojia; Zhan, Jiayu
Abstract: Subsequent to the sharp surge in quantity of municipal solid waste (MSW) generation, the pace at which waste treatment facilities are being constructed in some cities cannot meet the increasing demand for MSW treatment capacity. As a remedy to this, the co-processing of MSW in high-temperature cement kilns has become a potential MSW treatment option in emerging countries, and has been widely implemented in developed countries such as Netherlands and Germany. However, the environmental impacts of MSW co-processing in cement kilns differ from those of traditional treatment technologies. Besides, it is necessary to determine whether MSW co-processing in cement kilns could reduce the overall environmental impacts of MSW treatment and disposal as a whole, which is a key step in analyzing the feasibility of the treatment technology. Hence, this study used the life cycle assessment (LCA) method to quantitatively analyze the environmental impacts of MSW co-processing in cement kilns and the results further compared with other MSW treatment technologies. The functional unit was one ton of raw MSW, and real operational data from the cement industry and MSW treatment project in China was used for case studies. The results revealed that when compared to incineration and mechanical biological treatment (MBT), the environmental impact mitigation of energy recovery during MSW co-processing in cement kilns is not that significant. However, since there is no required additional treatment of residual waste and wastewater, the environmental impact caused by MSW co-processing in cement kiln appeared to be much lower from a life cycle perspective. Therefore, under conditions of insufficient MSW treatment capacity, co-processing in cement kiln could be an effective complementary approach to MSW management in China and other emerging countries which have many new dry cement kilns suitable for this alternative complementary technique of MSW treatment and disposal.